Epistemic Engineering and the Lucha for Sexual Rights in Postrevolutionary Nicaragua. (7th July 2013) - Howe, Cymene
Abstract From 1992 to 2007, Nicaragua had the dubious distinction of maintaining the most repressive antisodomy law in the Americas. Based upon several years of field research with activists involved in what they have called the lucha for sexual rights, this article considers the "epistemological engineering" of Nicaragua's sexual rights struggle. It discusses two distinct frameworks that have informed the work of advocacy: "Orgullo Lésbico‐gay" (Lesbian and Gay Pride) and "Una Sexualidad Libre de Prejuicios" (Sexuality Free from Prejudice)—both of which have different ideological origins and epistemological purposes. As managers of political logics and strategists of social struggle, activists have utilized political performances and publicly disseminated discourses in order to craft the way in which the struggle will "come out, " and ultimately how sexual rights will be understood by the larger Nicaraguan body politic. Through this process, activists have developed the epistemic dimensions of sexual rights in multiple registers, including those of universal liberation and minority rights, as well as earlier iterations of a communitarian ethos, including Sandinismo.